TEACHING VOCABULARY TO JUNIOR HIGH SCHOOL STUDENTS BY USING KICK ME TECHNIQUE - Afdal Yuliansyah; Fitrawati Fitrawati (Journal of English Language Teaching, 2016)
Vocabulary is an important factor in learning a language. People will not be able to listening, speaking, reading, and writing without mastering vocabulary. Also in learning English, vocabulary has an important role. However, not all of the Junior High School students learn vocabulary easily which is caused by the learning activity which is not really interesting for the students. Kick Me technique is astrategy which can be used by the teacher in teaching vocabulary to Junior High School students. Kick Me technique is an learning activity that students find the missing words in the worksheet on their classmates’ backs. Analogy and word relationships are given as a clue to finish it.